The convergent and divergent patterns in brain perfusion between Alzheimer's disease and Parkinson's disease with dementia: An ASL MRI study - Chen, Hongri; Xu, Yao; Chen, Lanlan; Shang, Songan; Luo, Xianfu; Wang, Xin; Xia, Wei; Zhang, Hongying (Frontiers in Neuroscience, 2022)
Abstract Background: Aberrant brain blood perfusion changes have been found to play an important role in the progress of Alzheimer’s disease (AD) and Parkinson's disease with dementia (PDD). However, the convergent and divergent patterns in brain perfusion between two dementias remains poorly documented. Objective: To explore the impaired brain perfusion pattern and investigate their overlaps and differences between AD and PDD by using normalized cerebral blood flow (CBF). Methods: The regional perfusion in patients with AD and PDD as well as healthy control (HC) subjects was explored using three-dimensional arterial spin labeling. The normalized CBF values were compared across the three groups and were further explored the potential linkages to clinical assessments. Results: In total, 24 patients with AD, 26 patients with PDD and 35 HC subjects were enrolled. Relative to HC group, both the AD group and PDD group showed reduced normalized CBF mainly in regions of temporal and frontal gyrus, whereas preserved perfusion presented in sensorimotor cortex and basal ganglia area. Comparing with AD group, PDD group showed decreased perfusion in the right putamen and right supplementary motor area (SMA), while preserved perfusion in the right inferior parietal lobule (IPL) and right precuneus. In the AD group, significant correlations were observed between the normalized CBF values in the right IPL and scores of global cognitive function (P = 0.033, ρ = 0.442), between the normalized CBF values in the right precuneus and the scores of memory function (P = 0.049，ρ = 0.406). The normalized CBF in the right putamen were significantly linked to cores of motor symptoms (P = 0.017, ρ = 0.214) in the PDD group. Conclusion: Our findings suggested convergent and divergent patterns of brain hemodynamic dysregulation between AD and PDD and contributed to a better understanding of the pathophysiological mechanisms.